Marvels of Bacilli in soil amendment for plant-growth promotion toward sustainable development having futuristic socio-economic implications - Mukhopadhyay, Meenakshi; Mukherjee, Ashutosh; Ganguli, Sayak; Chakraborti, Archisman; Roy, Samrat; Choudhury, Sudeshna Shyam; Subramaniyan, Vetriselvan; Kumarasamy, Vinoth; Sayed, Amany A.; El-Demerdash, Fatma M.; Almutairi, Mikhlid H.; Şuţan, Anca; et al. (Frontiers in Microbiology, 2023)
Microorganisms are integral components of ecosystems, exerting profound impacts on various facets of human life. The recent United Nations General Assembly (UNGA) Science Summit emphasized the critical importance of comprehending the microbial world to address global challenges, aligning with the United Nations Sustainable Development Goals (SDGs).In agriculture, microbes are pivotal contributors to food production, sustainable energy, and environmental bioremediation. However, decades of agricultural intensification have boosted crop yields at the expense of soil health and microbial diversity, jeopardizing global food security. To address this issue, a study in West Bengal, India, explored the potential of a novel multi-strain consortium of plant growth promoting (PGP) Bacillus spp. for soil bioaugmentation. These strains were sourced from the soil's native microbial flora, offering a sustainable approach. The study's findings demonstrated significant improvements in plant growth and soil microbial diversity when using the bacterial consortium in conjunction with vermicompost. Metagenomic analysis revealed increased abundance of many functional genera and metabolic pathways in consortium-inoculated soil, indicating enhanced soil biological health. Our study reported that a composite inoculum of Bacillus zhangzhouensis MMAM, Bacillus cereus MMAM3), and Bacillus subtilis MMAM2 could remarkably enhance soybean plant growth, yield performance and simultaneously enrich the beneficial bacterial composition in soil. This innovative bioaugmentation strategy to upgrade the overused agricultural soil through introduction of residual PGP bacterial members as consortia, presents a promising path forward for sustainable agriculture. Recognizing the significance of multi-strain PGP bacterial consortia as potential bioinoculants, such strategy, can bolster food security, enhance agricultural productivity, and mitigate the adverse effects of past agricultural activities.